A Retrospective Study of Socio-Demographic Profile and Pattern of Poisoning Cases at Tertiary Care Hospital - Vandana K; Siddesh Revpla Channabasappa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Death due to poisoning has been known since time immemorial. Poisoning is a major problem all over theworld, although its type and the associated morbidity and mortality vary from country to country. Accordingto the WHO, more than three million poisoning cases with 251,881 deaths occur worldwide annually, ofwhich 99% of fatal poisonings occur in developing countries, particularly among agricultural workers.Pattern of poisoning in any region depends on availability of poisons, socio economic status of the population,religious and cultural influences, occupation prevalent in the region and likewise. Organophosphoruspoisoning occurs very commonly in southern India, where farmers form a significant proportion of thepopulation who commonly use organophosphorus compounds like parathion as insecticides. A retrospectiveanalysis of all poisoning cases admitted to Saveetha Medical College Hospital, Chennai from Jan 2019to Dec 2019 was done to study the pattern of poisoning reported. Acute poisoning is a common medicalemergency and one of the important causes of morbidity and mortality in developing countries due to easyavailability of poisonous substances and its low cost. So, it was necessary to know the demo-graphic profile& pattern of poisoning cases at Saveetha Medical College Hospital, Chennai. Data was collected using apretested proforma from case records, MRD department & Emergency Medicine department and the datawas analyzed and presented.